Peptides with regularly alternating enantiomeric sequence: From ion channel models to bioinspired nanotechnological applications. Issue 5 (13th February 2018) - Novelli, Federica; De Santis, Serena; Morosetti, Stefano; Titubante, Mattia; Masci, Giancarlo; Scipioni, Anita
Abstract: Peptides are versatile building blocks that have been extensively used as peptide‐based organizers to generate bioinspired hybrid materials. Among them, those peptides characterized by regularly alternating enantiomeric sequences (l, d ‐peptides) have attracted much interest. Their structures, which are not accessible to the corresponding homochiral peptides, have been exploited to achieve hybrid conjugates, the chemical and structural properties of which can be predetermined by correct design. Molecules that self‐assemble into hollow tubular architectures with side chains on the outer surface can form, allowing the introduction of new functionalities on amino acid residues containing reactive side chains. This provides an effective strategy to develop engineered nanotubes with the surface suitably tuned for applications in different fields, spanning from electronics to medicine. Abstract :